KNOWLEDGE MANAGEMENT SYSTEM PENGOLAHAN SAMPAH MENGGUNAKAN SOCIALIZATION, EXTERNALIZATION, COMBINATION, INTERNALIZATION MODEL (INTI Nusa Mandiri, 2024)
Garbage is an environmental problem that cannot be avoided, changes in human lifestyles cause an increase in the volume of waste, various ways are carried out to overcome the increase in the volume of waste, one of which is the Reduce, Reuse, Recycle (3R) technique which plays an important role in waste processing and can change waste. to be artistic and economical, to share knowledge about waste management requires a container that can accommodate and share knowledge. In this study, a Knowledge Management System (KMS) was developed using the Knowledge Management Life Cycle (KMSLC) method and capturing knowledge using the Sosialization Externalization Combination Internalization (SECI) model. The results of this study are web-based applications that can accommodate, add and share knowledge in the form of tacit and explicit and change the knowledge formed from the results of individual interactions into documented knowledge which is expected to help organizations manage all knowledge and develop it so that it can improve the abilities and knowledge of members organization for waste management.
Keywords: 3R; garbage; KMSLC; KMS; SECI